Framing the EUDR in Indonesia: Elite Narratives, Marginalized Voices, and the Structural Limits of Environmental Journalism - Garnesia, Irma; Paramesthi, Twina (International Journal of Environmental Communication (ENVICOMM), 2025)
This study examines how Indonesian online media framed the European Union’s Deforestation-Free Regulation (EUDR) in 2023–2024. The EUDR, which mandates deforestation-free supply chains, has faced strong opposition from Indonesia, the world’s largest palm oil exporter, with officials accusing the EU of adopting a colonialist stance. Using a deductive quantitative content analysis of 273 news articles, we applied Semetko and Valkenburg’s framing model to identify dominant frames, news sources, and tone. Our findings show coverage was dominated by elite-driven narratives, episodic frames, and conflict-oriented reporting, focusing on political disputes and trade implications rather than systemic commodity governance. Smallholder farmers, those most affected by the regulation, were absent or represented only indirectly through associations. Government officials and industry dominated sourcing, while NGOs offered more thematic and nuanced perspectives but were marginal in mainstream reporting. These patterns reflect structural constraints in Indonesian journalism: oligarchic media ownership, market-driven content, and limited environmental expertise in newsrooms. We argue that these conditions narrow the scope of environmental journalism, reproducing official narratives while overlooking marginalized voices. The study also highlights the role of NGOs in providing alternative framings and calls for greater integration of their perspectives in reporting on transnational environmental policy.